Megatrends and sustainable cities - Alcocer Vela, Francis G. (2019)
Currently, the needs of people have been changing. Among these, the conventional notion of development by development or progress and hoarding as the mean to find happiness is being dismantled by new ways of seeing the world and conceptualizing it. One of them is the one that proposes sustainable spaces that observe development from a holistic and integral approach. This article is aimed at explaining what mega-tendencies are, how they relate to sustainablecities and how all these concepts relate to ethics. For this, the districts in Lima where the concept of a sustainable city has been applied are mentioned and develop.